Unique composite architecture of phosphor-in-glass film coated on different heat-conducting substrates for high-brightness laser lighting - Xin Liu; Mingxiang Chen; Jiuzhou Zhao; Hongjin Zhang; Yang Peng; Qing Wang (Journal of Advanced Ceramics)
In the development of static luminescent materials with remarkable optical-thermal performance and low cost, next-generation high-brightness laser lighting faces a key challenge. Herein, a unique composite architecture of Y3Al5O12:Ce3+ (YAG) phosphor-in-glass film coated on different heat-conducting substrates (PiGF@HCSs), i.e., PiGF@sapphire, PiGF@Al2O3, PiGF@AlN, and PiGF@BN–AlN composites, was designed and prepared by a simple film printing and low-temperature sintering technology. The heat-conducting substrates significantly affect the luminescence saturation and phosphor conversion of PiGF@HCSs, allowing substrates with higher thermal conductivity (TC) to have a higher laser power density (LPD) and higher reflectivity to enable higher luminous efficacy (LE). As a consequence, PiGF@sapphire realizes a luminous flux (LF) of 2076 lm@12 W/mm2, which is higher than those of PiGF@Al2O3 (1890 lm@15 W/mm2) and PiGF@AlN (1915 lm@24 W/mm2), whilePiGF@BN–AlN enables a maximum LF of 3058 lm@21 W/mm2. Furthermore, the LE of PiGF@BN–AlN reaches 194 lm/W, which is 1.6 times that of PiGF@AlN, while those of PiGF@sapphire and PiGF@Al2O3 are 192 and 150 lm/W, respectively. The working temperature of PiGF@AlN is only 93.3 °C under LPD of 9 W/mm2, while those of PiGF@sapphire, PiGF@Al2O3, and PiGF@BN–AlN increase to 193.8, 133.6, and 117 °C, respectively. These findings provide guidance for commercial applications of PiGF@HCS converters in high-brightness laser lighting and displays.